2012
DOI: 10.1097/hjh.0b013e3283544881
|View full text |Cite
|
Sign up to set email alerts
|

Stronger associations of obesity with prehypertension and hypertension in young women than in young men

Abstract: The results suggest that the associations of obesity with prehypertension and hypertension are stronger in women than in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…As reported by a cohort study, 50% of individuals aged>65 years with stage 2 prehypertension progressed to hypertension compared with 37% individuals aged<65 years . Similarly, Wakabayashi reported that the association of obesity with prehypertension or hypertension are greater in women than men . Moreover, another study showed that the effect of obesity (BMI > 27 kg/m 2 ) on the incidence of hypertension is stronger in women than in men .…”
Section: Discussionmentioning
confidence: 70%
“…As reported by a cohort study, 50% of individuals aged>65 years with stage 2 prehypertension progressed to hypertension compared with 37% individuals aged<65 years . Similarly, Wakabayashi reported that the association of obesity with prehypertension or hypertension are greater in women than men . Moreover, another study showed that the effect of obesity (BMI > 27 kg/m 2 ) on the incidence of hypertension is stronger in women than in men .…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, a greater change in SBP was noted among chronically obese white and Hispanic women compared to normal weight women than effects noted among White and Hispanic men. Gender differences in the association between obesity and hypertension have been previously noted 15 , however results have not been consistent, with some studies reporting a stronger association among men while others report stronger associations among women. The discrepancy in results could be due to the different age groups and ethnicities represented in these studies.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, the waist-to-height ratio (WHtR) has been proposed as a better screening tool than WC and BMI for adult cardiometabolic risk factors [5]. However, studies remain inconsistent with regard to the use of obesity indices, especially in Asia populations [6][9].…”
Section: Introductionmentioning
confidence: 99%